Perspectives on the role of teacher aides and the implications for inclusive practice in Aotearoa classrooms : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education (Inclusive Education) at Massey University, Albany, New Zealand - Woodhams, Claire M. (Massey University, 2018)
Every young person has the right to experience school, learning alongside their peers, building friendships with classmates and gaining a sense of autonomy. Teacher aides have traditionally been placed in classrooms to support students with disabilities and diverse learning and behavioural differences. An overreliance on teacher aide support, however, may lead to students becoming stigmatised and dependent. Through thematic analysis of interview data gathered from six teachers and eight teacher aides, supplemented by survey responses from 23 teachers 14 teacher aides, this thesis examines the perspectives on the teacher aide role and the implications for inclusive practice in Aotearoa classrooms. It identifies four prevalent role types perceived by participants, the teacher aides as: an aide to the teacher; a coeducator; a student aide (in class); and a student aide (outside class). Some roles, particularly the co-educator, are more conducive to social interaction and facilitating students’ independence. Others, particularly the student aide role, risk further isolating particular students. This thesis argues that it is teachers rather than teacher aides who are the primary agents of inclusive practice. As teachers adapt their practice to ensure that learning and achievement are possible for every student in their class, the need for one-on-one teacher aide support can be reduced. Teacher aides can work alongside teachers as co-educators overseeing the entire class, instructing small groups and checking-in with various students as needed, enabling teachers to work with students who benefit from more nuanced instruction. School leaders must examine the roles they assign to teacher aides and the associated practices in schools and classrooms. This will ensure that teacher aides are not viewed as the sole mechanisms for instructing and caring for students with disabilities and other diversities. Teacher aides are valuable members of the school community and can play a key role in contributing to inclusive practice in Aotearoa classrooms.
Keywords: Teachers' assistants; New Zealand; Inclusive education; Teachers; Attitudes